(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article analyzes the works of D.L. Ivanov of the late 19th century associated with the Pamirs. The concept of «Pamir» and the borders of the Pamirs, as defined by local residents, are considered. Geographical overview of the Pamirs. An indication of the indigenous population of the Kyrgyz in the Pamir proper. The name of individual genera and the background of their settlement. Physical type, nomadic economy, Kyrgyz methods of hunting for kiik, material culture and the administrative structure of the Kyrgyz.